Comparison of shaping ability of the Reciproc Blue and One Curve with or without glide path in simulated S-shaped root canals - Vincenzo Biasillo; Raffaella Castagnola; Mauro Colangeli; Claudia Panzetta; Irene Minciacchi; Gianluca Plotino; Simone Staffoli; Luca Marigo; Nicola Maria Grande (Restorative Dentistry & Endodontics, 2022)
ObjectivesThis study aimed to assess the impact of a glide-path on the shaping ability of 2 single-file instruments and to compare the centering ability, maintenance of original canal curvatures and area of instrumentation in simulated S-shaped root canals.Materials and MethodsForty simulated S-shaped root canals were used and were prepared with One Curve (group OC), One G and OC (group GOC), Reciproc Blue (group RB) and R-Pilot and RB (group PRB) and scanned before and after instrumentation. The images were analyzed using AutoCAD. After superimposing the samples, 4 levels (D1, D2, D3, and D4) and 2 angles (Δ1 and Δ2) were established to evaluate the centering ability and modification of the canal curvatures. Then, the area of instrumentation (ΔA) was measured. The data were analyzed using 2-way analysis of variance and Tukey's test for multiple comparisons (p < 0.05).ResultsRegarding the centering ability in the apical part (D3, D4), the use of the glide-path yielded better results than the single-file groups. Among the groups at D4, OC showed the worst results (p < 0.05). The OC system removed less material (ΔA) than the RB system, and for Δ1, OC yielded a worse result than RB (p < 0.05).ConclusionsThe glide-path improved the centering ability in the apical part of the simulated S-shaped canals. The RB system showed a better centering ability in the apical part and major respect of the canal curvatures compared with OC system.